UPAYA PEMANFAATAN LINGKUNGAN SEKITAR SEBAGAI SUMBER BELAJAR ANAK - Moh. Miftahul Choiri (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2017)
This article seeks to examine the child's learning environment. In education is better known as Tri Education Center. Namely three educational environments that can support the learning process of children. The three environments are the family environment, school environment and the environment (community). In the context of education, society is the third environment after family and school. In this article the authors would like to invite a look back that the community environment has an important influence on the learning process of children. Because most of the time the child is in the family and society. For it becomes a necessity of the community participate in education either directly or indirectly. Because the community is a maid in the process of maturation of individuals as members of groups in a society. The learning process in society is not limited by time and space. As long as the children interact and socialize with the environment it can be said that as their learning process. Through this library research hope can determine how far the role of the community environment in helping children's learning process.